Meta-Analysis: The Effects of Workload and Social Support on Burnout in Health Workers - Hanifah; Sumardiyono; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Burnout is a psychological syndrome of exhaustion, cynicism and ineffectiveness at work. Some factors causing burnout are workload and family support. The existence of a high workload can increase the incidence of burnout and high social support can prevent burnout in health workers. This study aims to estimate the effect of workload and social support on burnout in health workers. Subjects and Method: A systematic review and meta-analysis was carried out using the PRISMA guidelines and the PICO model covering Population = health workers; Intervention = high workload and high social support; Comparison = low workload and low social support; Outcome = burnout. Articles were collected from databases such as PubMed, Science Direct, and Google Schoolar. The keywords used in the database search were workload AND